Degradation of Chrysoidine Y Dye with Sulphite Ion in Aqueous Acidic Phase using Kinetic Method of Analysis - Patricia Umoru; Dr. Ikechukwu Ugbaga Nkole (Journal of Ata-Chem)
Chrysoidine Y dye (CYD) is harmful to aquatic species and human beings, which has the tendency to induce cancer and mutation to living cells. Its degradation is key in creating a healthy environment and curbing pollution. Hence, a stoichiometric method is used to study its degradation with a pool of sulphite ions (SO32-), under a constant ionic strength, [H+], and 449 nm wavelength. The stoichiometry is observed to be 1:1 for CYD: SO32-, which results in the formation of aniline and sulphonic acid as the main products of the degradation. The reaction is first-order with respect to CYD, first-order with respect to SO32-, and a second-order-overall. Increase in the proton concentration impacts positively on the reaction rate of CYD degradation. Negative salt effect is observed as the dilapidation rate of the dye drops. Occurrence of counter ion catalysis is pronounced with large appreciable rate. The participation of a firm intermediate molecule is negative as revealed by the Spectroscopic Scanning Technique (SST) and Michaelis Menten’s Type Plot (MMTP), which cancels the inner-sphere mechanism expectancy. The degradation of the dye was successfully carried out and the reaction points to the outer-sphere mechanism.